2019
DOI: 10.1016/j.alcohol.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Processing transdermal alcohol concentration (TAC) data to detect low-level drinking

Abstract: Reliance upon the AMS criteria for alcohol detection affords a high specificity for detection of heavy drinking but is a poor indicator of abstinence rates. In contrast use of our Research Rules provides more sensitive means to quantify either any drinking or low-moderate levels of drinking while still maintaining good specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 22 publications
2
54
0
Order By: Relevance
“…Abbreviations within the table are as follows: (e)BrAC, (estimated) breath alcohol concentration; SD, standard deviation; TAC, transdermal alcohol concentration; time, time of peak in hours. the SCRAM) or criteria as developed by researchers themselves (Roache et al, 2019). Roache and colleagues (2015) investigated the sensitivity of 2 versions of the SCRAM (SCRAMII and SCRAMx) in detecting low-level drinking when using different thresholds: (i) TAC > 0.00 g/dl, (ii) TAC > 0.02 g/dl, and (iii) TAC > 0.03 g/dl (Table 7).…”
Section: Studies Using Scrammentioning
confidence: 99%
See 2 more Smart Citations
“…Abbreviations within the table are as follows: (e)BrAC, (estimated) breath alcohol concentration; SD, standard deviation; TAC, transdermal alcohol concentration; time, time of peak in hours. the SCRAM) or criteria as developed by researchers themselves (Roache et al, 2019). Roache and colleagues (2015) investigated the sensitivity of 2 versions of the SCRAM (SCRAMII and SCRAMx) in detecting low-level drinking when using different thresholds: (i) TAC > 0.00 g/dl, (ii) TAC > 0.02 g/dl, and (iii) TAC > 0.03 g/dl (Table 7).…”
Section: Studies Using Scrammentioning
confidence: 99%
“…These criteria are necessarily conservative due to their use in the justice system and the legal implications associated with false positives. Further, the TAC data often show unnatural spikes that are likely caused by environmental noise, which require careful and considerate processing to ensure that we are reviewing alcohol consumption and not environmental noise (Roache et al, 2019). This is especially true of the SCRAM which only samples every 30 minutes, making it difficult to conclude whether a spike is environmental noise, a result of sudden temperature or humidity change, or movement for example.…”
Section: Processing Of Tac Data Including Criteria and Thresholds Usmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in many false negatives when compared to self‐report of drinking in community samples, particularly for light drinking episodes (Barnett et al., ; Dougherty et al., ). Accordingly, researchers have begun to develop and evaluate more liberal criteria sets to more completely capture drinking events in basic research (Barnett et al., ; Roache et al., ) and tools for processing and interpreting SCRAM data (Barnett et al., ). Investigations using WrisTAS have employed varying approaches, including a mathematical filtering scheme (Rosen et al., ) and differing thresholds on peak TAC (Marques and McKnight, ; Simons et al., ) to identify drinking events.…”
Section: Transdermal Alcohol Sensorsmentioning
confidence: 99%
“…Studies applying varying episode detection rules to SCRAM data have reported correctly identifying between 39.9 and 87.7% of drinking events observed in the laboratory or reported by drinkers in the field (Barnett et al., , ; Karns‐Wright et al., ; Marques and McKnight, ; Neville et al., ; Roache et al., ). Drinking events undetected by SCRAM tend to be those involving lower levels of consumption (e.g., 1 to 4 drinks; Barnett et al., ; Karns‐Wright et al., ; Roache et al., , ). In studies using WrisTAS, TAC data have detected between 23.6 and 85.6% of drinking events identified by other means (Bond et al., ; Marques and McKnight, ; Simons et al., ).…”
Section: Transdermal Alcohol Sensorsmentioning
confidence: 99%